2019
DOI: 10.1128/jvi.02063-18
|View full text |Cite
|
Sign up to set email alerts
|

The Glucocorticoid Receptor (GR) Stimulates Herpes Simplex Virus 1 Productive Infection, in Part Because the Infected Cell Protein 0 (ICP0) Promoter Is Cooperatively Transactivated by the GR and Krüppel-Like Transcription Factor 15

Abstract: Following acute infection, herpes simplex virus 1 (HSV-1) establishes lifelong latency in neurons. Physical, emotional, and chemical stresses are linked to increasing the incidence of reactivation from latency, but the mechanism of action is not well understood. In general, stress increases corticosteroid levels, leading to activation of the glucocorticoid receptor (GR), a pioneer transcription factor. Consequently, we hypothesized that stress-mediated activation of the GR can stimulate productive infection an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 45 publications
2
36
0
Order By: Relevance
“…The results of this study demonstrated that explant-induced reactivation from latency was stimulated by the synthetic corticosteroid DEX but was significantly reduced by a GR-specific antagonist (CORT-108297). CORT-108297 also significantly reduced viral replication in cultured cells (65), consistent with TG explant findings. Previous studies reported DEX accelerated explant-induced reactivation (21,22); however, these studies may have underestimated the effects of adding DEX to TG explants, because FBS was used in the studies.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The results of this study demonstrated that explant-induced reactivation from latency was stimulated by the synthetic corticosteroid DEX but was significantly reduced by a GR-specific antagonist (CORT-108297). CORT-108297 also significantly reduced viral replication in cultured cells (65), consistent with TG explant findings. Previous studies reported DEX accelerated explant-induced reactivation (21,22); however, these studies may have underestimated the effects of adding DEX to TG explants, because FBS was used in the studies.…”
Section: Discussionsupporting
confidence: 84%
“…A VP16 coactivator, host cell factor 1 (HCF-1), also localizes to the nucleus during explant-induced reactivation from latency (88), suggesting VP16 can transactivate IE gene expression during early stages of reactivation. Although the proximal VP16, ICP0, and ICP4 promoters do not contain consensus "whole" GREs, the ICP0 promoter is cooperatively transactivated by GR, DEX, and Krüppel-like transcription factor 15 (65). A 1 ⁄2 GRE in ICP0 promoter sequences was important for DEX-induced transcription mediated by GR and KLF15, suggesting multiple stress-induced factors are important for activating viral gene expression during early stages of reactivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Receptors Reflecting their well-documented roles in the response to CoV infection 18-21 , we observed appreciable significant intersections between CoV HCTs and those of the [22][23][24][25][26] . The Notch 9 receptor HCT intersection points to a possible mechanistic basis for the potential of Notch pathway modulation in the treatment of SARS2 27 .…”
Section: To Illuminate Human Signaling Pathways Orchestrating the Tramentioning
confidence: 58%
“…It has been revealed that stress increases corticosteroid levels, leading to activation of the glucocorticoid receptor (GR). The activated GR stimulates HSV-1 productive infection, in part because the ICP0 promoter is cooperatively transactivated by the GR and Krüppel-like transcription factor 15 (KLF15) 8 .…”
Section: Introductionmentioning
confidence: 99%